The Optimization of Digitalization in Facing Global Competition: The Case of Islamic Accounting - Kamilah K.; Yenni Samri Juliati Nasution (Qubahan Academic Journal)
Analyzing the optimization that needs to be done from the digital aspect of Islamic accounting to improve student competence to compete in the world of work according to company needs. This study investigates and analyzes this based on the perspective of Islamic accounting graduate students as a workforce and the perspective of company stakeholders as employers. They are using a qualitative descriptive approach. In-depth interviews with research participants collected data and then analyzed using the Miles and Huberman model. The findings show that it is essential for Islamic higher education to integrate technology into the learning process. Make adjustments to meet the needs of the company and the learning provided. The most proposed optimization towards the digitalization of Islamic accounting is using accounting software, Microsoft Excel, digital literacy regarding financial technology, and AI. These proposals are significant in shaping the readiness of graduates to compete in an increasingly competitive world of work. This research contributes to providing an overview of digitalization that needs to be optimized by Islamic higher education according to the needs of Islamic accounting graduates as a workforce and company stakeholders as employers. Islamic higher education can then use this picture to shape student competencies to be ready to compete in the world of work.